The top nations in the medal table of the current Olympic Games - Shvetsov, A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the ranking of teams in the medal table and the contribution of athlete training systems in Olympic sports among the nations that have achieved the most success in the modern Olympic Games.